Importance of two PDZ domains for the proteolytic and chaperone activities of Helicobacter pylori serine protease HtrA - Zarzecka, Urszula; Matkowska, Dorota; Backert, Steffen; Skorko-Glonek, Joanna (Cellular Microbiology, 2020)
The Helicobacter pylori HtrA protein (HtrAHp) is an important virulence factor involved in the infection process by proteolysis of components of the tight (claudin-8 and occludin) and adherens junctions (E-cadherin) between epithelial cells. As a protease and chaperone, HtrAHp is involved in protein quality control, which is particularly important under stress conditions. HtrAHp contains a protease domain and two C-terminal PDZ domains (PDZ1 and PDZ2). In the HtrA protein family, the PDZ domains are proposed to play important roles, including regulation of proteolytic activity. We therefore mutated the PDZ1 and PDZ2 domains in HtrAHp and studied the maintenance of proteolytic activity, assembly and rearrangement of the corresponding oligomeric forms. Our in vitro experiments demonstrated that at least PDZ1 is important for efficient substrate cleavage, while both PDZ domains are dispensable for the chaperone-like activity. However, in living H. pylori cells, only the mutant containing at least PDZ1, but not PDZ2, ensured bacterial growth under stressful conditions. Moreover, we can demonstrate that PDZ1 is crucial for HtrAHp oligomerization. Interestingly, all truncated proteolytically active HtrAHp variants were functional in the in vitro infection assay and caused damage to the E-cadherin-based adherens junctions. These findings provide valuable new insights into the function of HtrAHp in an important pathogen of humans.
CRIS-Team Scopus Importer:2020-12-25
Keywords: chaperone; E-cadherin; Helicobacter pylori; HtrA; oligomerization; PDZ domain; protease; stress endurance